DINAMIKA PERKEMBANGAN TAFSIR AL-QUR’AN SECARA TEKSTUAL DAN KONTEKSTUAL - Fajar, Ali; Hanah, Far; Masyhur, Laila Sari; Aminullah, Muhammad (Universitas Islam Negeri Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2025)
The interpretation of the Qur'an has continuously adapted over time, transitioning from a literal, text-centered approach to a more contextual method that aligns with contemporary social dynamics and scientific progress. The literalist approach concentrates on the direct linguistic meaning of the Qur'anic verses, drawing support from hadith and classical scholarly interpretations. Meanwhile, the contextual approach prioritizes understanding the Qur'an within its historical, societal, and cultural settings to extract meanings that resonate with modern-day realities. This study utilizes a qualitative literature review to explore the historical development of Qur'anic interpretive methods in Islamic thought. The results highlight that blending textual and contextual perspectives fosters a deeper and more holistic comprehension of the Qur’an. Such integration is crucial for developing interpretative models that are both true to the sacred text and adaptable to current times. Consequently, the ongoing refinement of interpretive methodologies is vital to ensure that the Qur'an continues to serve as a relevant and practical guide for humanity.